Independent inhibition of the polymerase and deubiquitinase activities of the Crimean-Congo Hemorrhagic Fever Virus full-length L-protein. - Egor P Tchesnokov; Ben A Bailey-Elkin; Brian L Mark; Matthias Götte (Public Library of Science (PLoS), 2020)
BACKGROUND:The Crimean-Congo hemorrhagic fever virus (CCHFV) is a segmented negative-sense RNA virus that can cause severe human disease. The World Health Organization (WHO) has listed CCHFVas a priority pathogen with an urgent need for enhanced research activities to develop effective countermeasures. Here we adopted a biochemical approach that targets the viral RNA-dependent RNA polymerase (RdRp). The CCHFV RdRp activity is part of a multifunctional L protein that is unusually large with a molecular weight of ~450 kDa. The CCHFV L-protein also contains an ovarian tumor (OTU) domain that exhibits deubiquitinating (DUB) activity, which was shown to interfere with innate immune responses and viral replication. We report on the expression, characterization and inhibition of the CCHFV full-length L-protein and studied both RNA synthesis and DUB activity. METHODOLOGY/PRINCIPLE FINDINGS:Recombinant full-length CCHFV L protein was expressed in insect cells and purified to near homogeneity using affinity chromatography. RdRp activity was monitored with model primer/templates during elongation in the presence of divalent metal ions. We observed a 14-mer full length RNA product as well as the expected shorter products when omitting certain nucleotides from the reaction mixture. The D2517N mutation of the putative active site rendered the enzyme inactive. Inhibition of RNA synthesis was studies with the broad-spectrum antivirals ribavirin and favipiravir that mimic nucleotide substrates. The triphosphate form of these compounds act like ATP or GTP; however, incorporation of ATP or GTP is markedly favored over the inhibitors. We also studied the effects of bona fide nucleotide analogues 2'-deoxy-2'-fluoro-CTP (FdC) and 2'-deoxy-2'-amino-CTP and demonstrate increased inhibitory effects due to higher rates of incorporation. We further show that the CCHFV L full-length protein and the isolated OTU domain cleave Lys48- and Lys63-linked polyubiqutin chains. Moreover, the ubiquitin analogue CC.4 inhibits the CCHFV-associated DUB activity of the full-length L protein and the isolated DUB domain to a similar extent. Inhibition of DUB activity does not affect elongation of RNA synthesis, and inhibition of RNA synthesis does not affect DUB activity. Both domains are functionally independent under these conditions. CONCLUSIONS/SIGNIFICANCE:The requirements for high biosafety measures hamper drug discovery and development efforts with infectious CCHFV. The availability of full-length CCHFV L-protein provides an important tool in this regard. High-throughput screening (HTS) campaigns are now feasible. The same enzyme preparations can be employed to identify novel polymerase and DUB inhibitors.